ANALISIS TERHADAP PERILAKU BERTRANSAKSI ONLINE PENGGUNA FACEBOOK COMMERCE - Vivi Sahfitri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
The concept of electronic commerce is widely used today's society, or better known as e-commerce, information technology was born as globalization in economics. Social networking is one of the media of electronic commerce, which currently has a lot of users. The purpose of this study was to examine factors that influence e-commerce user on social networks, one of which is the facebook for online transactions. Data analysis performed in this study using multiple linear regression techniques to look at the variables that affect behavior variables commerce facebook users either partially or simultaneously. The results of this study are expected to provide empirical evidence about the factors that influence the behavior of users of facebook commerce in conducting online transactions. In addition the test results are also expected to give evidence about the dominant factors that influence user behavior in online transactions through social networking media.